2020
DOI: 10.1021/acssensors.0c01609
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoelectrochemical Detection of an Analyte Triggered by Its Concentration by a Singlet Oxygen-Generating Fluoro Photosensitizer

Abstract: The use of a photocatalyst (photosensitizer) which produces singlet oxygen instead of enzymes for oxidizing analytes creates opportunities for designing cost-efficient and sensitive photoelectrochemical sensors. We report that perfluoroisopropyl-substituted zinc phthalocyanine (F64PcZn) interacts specifically with a complex phenolic compound, the antibiotic rifampicin (RIF), but not with hydroquinone or another complex phenolic compound, the antibiotic doxycycline. The specificity is imparted by the selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Most of the previously reported PEC sensors rely on a photoinduced electron transfer from a PS to a semiconductor, followed by an electron transfer from the semiconductor to an electrode, Figure A. The electrode, in this case, is polarized accordingly to play the role of the electron acceptor (anode). We have recently reported a different PEC sensing approach, namely the use of a PS to generate analyte-oxidizing singlet oxygen, 1 O 2 , Figure B. ,,, The used PS, F 64 PcZn, Figure D, contains bulky, perfluorinated iso-propyl peripheral substituents that ensure it remains a single-site catalyst both in solution and solid-state films, and resists the destructive action of 1 O 2 and its daughter radicals . Notably, the supporting TiO 2 semiconductor is not subject to electron injection from the photoexcited F 64 PcZn due to the electron-withdrawing effect of fluorine substituents that stabilize the LUMO by more than 1 eV , relative to PcZn, Figure C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previously reported PEC sensors rely on a photoinduced electron transfer from a PS to a semiconductor, followed by an electron transfer from the semiconductor to an electrode, Figure A. The electrode, in this case, is polarized accordingly to play the role of the electron acceptor (anode). We have recently reported a different PEC sensing approach, namely the use of a PS to generate analyte-oxidizing singlet oxygen, 1 O 2 , Figure B. ,,, The used PS, F 64 PcZn, Figure D, contains bulky, perfluorinated iso-propyl peripheral substituents that ensure it remains a single-site catalyst both in solution and solid-state films, and resists the destructive action of 1 O 2 and its daughter radicals . Notably, the supporting TiO 2 semiconductor is not subject to electron injection from the photoexcited F 64 PcZn due to the electron-withdrawing effect of fluorine substituents that stabilize the LUMO by more than 1 eV , relative to PcZn, Figure C.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported a different PEC sensing approach, namely the use of a PS to generate analyte-oxidizing singlet oxygen, 1 O 2 , Figure 2B. 6,11,30,35 The used PS, F 64 PcZn, Figure 1D, contains bulky, perfluorinated iso-propyl peripheral substituents that ensure it remains a single-site catalyst both in solution and solid-state films, and resists the destructive action of 1 O 2 and its daughter radicals. 36 Notably, the supporting TiO 2 semiconductor is not subject to electron injection from the photoexcited F 64 PcZn due to the electron-withdrawing effect of fluorine substituents that stabilize the LUMO by more than 1 eV 37,38 relative to PcZn, Figure 1C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This can be explained not only by the fact that electrochemical methods have the advantage of being relatively simple, rapid and cheap, but also through the multitude of materials and procedures that allow for the modification of the electrode surface in order to achieve more sensitive and selective determinations. Comparing the RIF therapeutic peak plasma concentration of 8–24 µg/mL (9.72 × 10 −6 –2.92 × 10 −5 mol/L RIF) [ 159 ] with the linear ranges of the electrochemical methods reported in the last 20 years for RIF quantification ( Table 1 ), it can be observed that, with one exception [ 90 ], all these methods could be applied to RIF blood level monitoring, most of them [ 19 , 25 , 26 , 27 , 28 , 36 , 45 , 50 , 52 , 56 , 65 , 66 , 67 , 83 , 84 , 86 , 88 , 104 , 106 , 111 , 112 , 114 , 115 , 116 , 117 , 120 , 121 ] needing a previous dilution step to bring RIF concentration into the linear range of the method. UV-Vis spectrometric methods present narrower linear ranges and are less sensitive; therefore, according to the data summarized in Table 2 , most RIF determinations based on absorbance measurements may be applied as reported for the assessment of RIF blood concentration.…”
Section: Discussionmentioning
confidence: 99%
“…RIF and RSV ( Figure 1 ) are hydroquinone derivatives (−OH groups in positions 1 and 4, Figure 1 ) and possess a third phenolic −OH moiety (position 8), which can be chemically or electrochemically oxidized [ 40 ] at various solid bare electrodes (e.g., GCE [ 85 ], CPE [ 80 ] and the disposable PGE [ 84 ]) or modified sensors obtained at various substrates, such as GCE [ 28 , 29 , 32 , 37 , 45 , 52 , 65 , 66 , 67 , 68 , 85 , 90 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 121 ], SPE [ 36 , 53 , 115 ], CPE [ 21 , 26 , 80 , 88 , 116 , 117 ], ITO [ 118 ], Ag [ 55 ], Au [ 50 , 86 ] and Pt [ 119 , 120 ]. Most often, the electrodes were employed as sensing devices in voltammetric [ 26 , 27 , 28 , 31 , 36 , …”
Section: Rifamycins Detection and Monitoringmentioning
confidence: 99%
“…electrode surface is a challenging process, but an efficient way to achieve this involves an incubation step where the compound is accumulated near the surface. 55 Such a method mostly works with large phenolic compounds with low solubility in water such as rifampicin; 56 yet smaller compounds such HQ do not incubate at the surface as they are easily removed by washing the surface.…”
Section: Laser On Laser Offmentioning
confidence: 99%